Mechanical and degradation property improvement in a biocompatible Mg-Ca-Sr alloy by thermomechanical processing. (April 2018) - Henderson, Hunter B.; Ramaswamy, Vidhya; Wilson-Heid, Alexander E.; Kesler, Michael S.; Allen, Josephine B.; Manuel, Michele V.
Abstract: Magnesium-based alloys have attracted interest as a potential material to comprise biomedical implants that are simultaneously high-strength and temporary, able to provide stabilization before degrading safely and able to be excreted by the human body. Many alloy systems have been evaluated, but this work reports on improved properties through hot extrusion of one promising alloy: Mg-1.0 wt% Ca-0.5 wt%Sr. This alloy has previously demonstrated promising toxicity and degradation properties in the as-cast and rolled conditions. In the current study extrusion causes a dramatic improvement in the mechanical properties in tension and compression, as well as a low in vitro degradation rate. Microstructure (texture, second phase distribution, and grain size), bulk mechanical properties, flow behavior, degradation in simulated body fluid, and effect on osteoblast cyctotoxicity are evaluated and correlated to extrusion temperature. Maximum yield strength of 300 MPa (above that of annealed 316 stainless steel) with 10% elongation is observed, making this alloy competitive with existing implant materials. Graphical abstract: fx1 Highlights: Significant improvements in crucial properties for biomedical Mg alloys are observed by hot extrusion of a Mg-1.0 wt% Ca-0.5 wt%Sr alloy. By varying extrusion temperature, a range of microstructures and strength levels are obtained, including yield strength of 300 MPa with substantial ductility. Low degradation rate and cytotoxicity are also observed, making this alloy appropriate for human biomedical devices.